2021
DOI: 10.1111/pan.14279
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety in preschool children: A randomized clinical trial comparing midazolam, clonidine, and dexmedetomidine

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 31 publications
0
34
1
Order By: Relevance
“…While many drugs have been explored in an effort to reduce preoperative anxiety, induce preoperative sedation and facilitate anesthesia induction, no such labelling was granted until recently. None of the major drug classes known to offer pertinent effects (benzodiazepines, NMDA-receptor antagonists, alpha-2-receptor agonists) meet all the requirements for preoperative pharmacological use in children, nor are they labelled for this specific indication [ 1 , 3 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many drugs have been explored in an effort to reduce preoperative anxiety, induce preoperative sedation and facilitate anesthesia induction, no such labelling was granted until recently. None of the major drug classes known to offer pertinent effects (benzodiazepines, NMDA-receptor antagonists, alpha-2-receptor agonists) meet all the requirements for preoperative pharmacological use in children, nor are they labelled for this specific indication [ 1 , 3 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Premedication administered before surgery to reduce stress and facilitate the induction of anesthesia plays an important role in the perioperative management of children [ 1 , 2 ]. Midazolam with its sedative [ 3 ], anxiolytic [ 1 ] and amnesic [ 4 ] effects is a popular drug for these applications and has shown its efficacy in reducing anxiety and in providing adequate sedation [ 3 ]. Strictly speaking, however, midazolam is an intravenous formulation.…”
Section: Introductionmentioning
confidence: 99%
“…While controlled studies are challenging, longstanding clinical experience indicates that rapid reduction of anxiety by benzodiazepines can mitigate the arrhythmogenic effects of increased circulating levels of catecholamines on a damaged cardiac conduction system in anxious or frightened patients with acute myocardial infarction [79]. Benzodiazepines are appropriate for rapid control of anxiety in anticipation of surgery and other procedures or in response to acute injury or illness in children as well as adults [80, 81]. In the absence of any potential return on investment for studies of medications that are off patent, no recent therapeutic studies of benzodiazepines in anxiety have been conducted.…”
Section: Clinical Applications Of Benzodiazepines and Z-drugsmentioning
confidence: 99%
“…Although sedative effects can be obtained by oral administration, there is no consensus on factors other than pharmacokinetics related to sedative effects and on the characteristics of the children in whom it is difficult to obtain a sedative effect. Bromfalk et al 9 reported that preschoolers likely showed higher anxiety due to differences in the pharmacokinetics and an interaction with the nonpharmacological components of the preanesthetic milieu.…”
Section: Introductionmentioning
confidence: 99%